1984
DOI: 10.1016/0021-9797(84)90079-1
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography as a technique to measure the competitive adsorption of plasma proteins onto latices

Abstract: Isotherms of human serum albumin (HSA), human immunoglobulin G (HIgG), and human fibrinogen (HFb) onto a polystyrene (PS)-latex were determined by depletion of protein in the solution, which was either followed by radioactivity measurements or by UV spectroscopy. Different adsorption isotherms for the same protein were obtained when either radioactivity measurements or UV spectroscopy was used as a detection technique. In order to obtain reliable results from competitive protein adsorption experiments, a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…However, labeling may change the conformation stability of proteins, and affect their adsorption behavior or even promote aggregation in proteins [87,95,96]. To avoid the adverse effects of labeling, other "label-free" tools have been employed such as size exclusion chromatography [87,95,96], electrophoresis [128], ellipsometry [132,133], spectroscopy [134], surface plasmon resonance [101], quartz crystal microbalance [135], tensiometry [132], reflectrometry [136], shear rheology [125], surface force apparatus [137] and imaging techniques [138]. However, there are only a few reports where these tools have been employed on oligomers (monomers, dimers etc) of the same protein [87][88][89].…”
Section: Oligomeric Protein Adsorption-desorption To Es Silica Capillmentioning
confidence: 99%
See 2 more Smart Citations
“…However, labeling may change the conformation stability of proteins, and affect their adsorption behavior or even promote aggregation in proteins [87,95,96]. To avoid the adverse effects of labeling, other "label-free" tools have been employed such as size exclusion chromatography [87,95,96], electrophoresis [128], ellipsometry [132,133], spectroscopy [134], surface plasmon resonance [101], quartz crystal microbalance [135], tensiometry [132], reflectrometry [136], shear rheology [125], surface force apparatus [137] and imaging techniques [138]. However, there are only a few reports where these tools have been employed on oligomers (monomers, dimers etc) of the same protein [87][88][89].…”
Section: Oligomeric Protein Adsorption-desorption To Es Silica Capillmentioning
confidence: 99%
“…This effect has been observed in both stagnant [83,84] and low shear flow conditions (≈ 500 sec -1 , 225 sec -1 to 2700 sec -1 ) [85,86]. However, with a few exceptions, [87][88][89] there seems to be an overall lack of tools that can study adsorption-desorption of oligomers of same protein other than a few exceptions. Furthermore, it is common to label proteins while studying multi-protein systems or sequential adsorption [92][93][94] despite the fact that labeling may change conformational stability of proteins and also affect adsorption patterns [95][96][97].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This phenomenon, which is representative of what has been termed the "Vroman effect," has been demonstrated by Vroman and Adams (3) for fibrinogen. In studies involving fibrinogen, IgG, and albumin at long adsorption times, it is observed that the preference for the adsorbent surface decreases in this order (4,5). Nevertheless, when comparing the adsorption affinity of proteins ofdifferent sizes, the differences in their electrical charge and conformational stability and in their hydrophobicity or that of the surface must also be taken into account.…”
mentioning
confidence: 99%
“…41932) was obtained from Serva and characterized as described earlier [13]. Specific surface area 15 m:/g; poly-styrene content 10% (w/w); density 1.0 g/l; diameter latex particles 399 nm according to scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%